2017
DOI: 10.1101/199760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Idiosyncratic genome degradation in a bacterial endosymbiont of periodical cicadas

Abstract: When a free-living bacterium transitions to a host-beneficial endosymbiotic lifestyle, it almost invariably loses a large fraction of its genome [1,2]. The resulting small genomes often become unusually stable in size, structure, and coding capacity [3][4][5]. Candidatus Hodgkinia cicadicola (Hodgkinia), a bacterial endosymbiont of cicadas, sometimes exemplifies this genomic stability. The Hodgkinia genome has remained completely co-linear in some cicadas diverged by tens of millions of years [6,7]. But in the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 70 publications
0
15
1
Order By: Relevance
“…Nevertheless, it is possible that the jigsaw of nutritional contributions was largely shaped by genetic drift as the random corruption and loss of some nutritional pathways in a particular symbiont forced complementation in another. Several recent studies have highlighted the underlying role of drift in driving lineage specific gene losses and in shaping the co-evolution of host-symbiont interactions (Boscaro et al, 2017;Campbell et al, 2017;Sabater-Muñoz et al, 2017). Thus, as the genomes of the early bacterial symbionts in Auchenorrhyncha began to unravel, stochastic gene losses and partner complementation may have caused the bacterial symbionts to spiral down their own pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is possible that the jigsaw of nutritional contributions was largely shaped by genetic drift as the random corruption and loss of some nutritional pathways in a particular symbiont forced complementation in another. Several recent studies have highlighted the underlying role of drift in driving lineage specific gene losses and in shaping the co-evolution of host-symbiont interactions (Boscaro et al, 2017;Campbell et al, 2017;Sabater-Muñoz et al, 2017). Thus, as the genomes of the early bacterial symbionts in Auchenorrhyncha began to unravel, stochastic gene losses and partner complementation may have caused the bacterial symbionts to spiral down their own pathways.…”
Section: Resultsmentioning
confidence: 99%
“…For many endosymbionts, a process similar to mitochondrial and plastid genome reduction occurs. The initially free‐living bacterium loses most of its genome and transitions to “a host‐beneficial endosymbiotic lifestyle.” The reduced endosymbiont genomes typically stabilize in size, structure, and coding capacity. In some cases, descendants of a single obligate endosymbiotic bacterium can diverge into complementary intracellular constituents by losing different parts of the initial endosymbiont genome …”
Section: Additional Cell Fusions In Evolutionary Historymentioning
confidence: 99%
“…In many of the cicada species characterized to date (but see (13)), these nutritional services are provided by two transovarially transmitted bacterial endosymbionts, Candidatus Sulcia muelleri (hereafter referred to as Sulcia) and Candidatus Hodgkinia cicadicola (hereafter Hodgkinia) (14)(15)(16). We have previously shown that in two cicada genera, Tettigades and Magicicada, Hodgkinia has undergone an unusual form of lineage splitting (17)(18)(19)(20). In some of these cicada species, a single Hodgkinia lineage has split into two or more derived lineages, each containing only a subset of the genes present in the single ancestral lineage.…”
Section: Introductionmentioning
confidence: 99%
“…The number of Hodgkinia lineages varies in different cicada species. For example, a species in the cicada genus Diceroprocta has one Hodgkinia lineage (21), various species in the genus Tettigades have between one and six Hodgkinia lineages (17,20), and the seven species in the long-lived periodical genus Magicicada contain more, possibly dozens, of Hodgkinia lineages (18,19).…”
Section: Introductionmentioning
confidence: 99%